Development of Creative Ability of Future it Teachers - Khayriyeva Shahnoza Saydullo kizi (Genius Journals, 2023)
This article information about presents suggestions and recommendations on ways to develop the creative abilities of young computer science teachers, and how to overcome them.
Keywords: Creativity; cloud technology; Internet